Estimates of the Size and Source of Price Declines Due to Nearby Foreclosures - Anenberg, Elliot; Kung, Edward (American Economic Review, 2014)
Using new data on real estate listings, we provide new evidence that foreclosures have a causal effect on nearby house prices and disentangle the effect into two sources: competition and disamenities. We identify the causal effect by showing that sellers respond to new REO listings in the exact week of listing, not a week before and not a week after. We disentangle competition and disamenity effects by examining the spillover effect across various stages of the foreclosure process. We find that competition effects are important in all areas, but only find evidence for disamenity effects in high density, low price neighborhoods. (JEL R31)